Sistem Informasi Potensi Kependudukan Desa Sukajulu Berbasis Web - Ginting, Monika; Pakpahan, Sorang (MEANS (Media Informasi Analisa dan Sistem), 2018)
Village Potential is the whole of the resources owned or used by the village both human resources (HR), natural resources (SDA) and institutions or infrastructure and facilities to support the acceleration of community welfare. However, in notifying the potential possessed by Sukajulu village, it has not been able to be understood quickly because it does not yet have a village potential website. Where village officials still have difficulties in providing potential information to village communities and the wider community. So with the above problems, the writer wants to build a potential information system of Sukajulu Village that will facilitate village officials in inputting village potential data inputs and make it easier to publish Village data, especially in Sukajulu Village, by utilizing computer applications that have been created and can convey information quickly and accurately for both the village community and the wider community who need information about the potential of Sukajulu Village